2022
DOI: 10.17275/per.22.46.9.2
|View full text |Cite
|
Sign up to set email alerts
|

The role of technological pedagogical content knowledge and social cognitive variables in teachers’ technology integration behaviors

Abstract: The Technological Pedagogical Content Knowledge (TPACK) framework provides a theoretical perspective of showing whether a teacher can effectively design and conduct technology-enhanced instruction. In addition, social cognitive variables like self-efficacy, outcome expectations, interest and intentions play a vital role in whether teachers choose to integrate technology into their instructional practices. Therefore, this study aimed to investigate the relationships between TPACK dimensions and these social cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…These findings contribute to the body of knowledge on using ICTs for teaching. For instance, the foregoing results are contrary to the findings of Dikmen (2021), which revealed that PK, CK and PCK are not significant predictors of using ICTs in their path modelling for technology integration in teaching.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…These findings contribute to the body of knowledge on using ICTs for teaching. For instance, the foregoing results are contrary to the findings of Dikmen (2021), which revealed that PK, CK and PCK are not significant predictors of using ICTs in their path modelling for technology integration in teaching.…”
Section: Discussioncontrasting
confidence: 95%
“…Furthermore, an interesting result of the current study was that access to ICT resources does not seem to be a determining factor that mathematics and science teachers will use ICTs. What makes this finding to be particularly interesting is that if teacher educators are intentional in developing the necessary knowledge domains needed for ICT use for teaching, it suggests that, despite the lack of ICTs resources which is common in many schools (Dikmen, 2021), teachers with developed ICT competency may always find possible ways to leverage on the potential of ICTs to enhance their pedagogy.…”
Section: Discussionmentioning
confidence: 99%
“…Following Valverde et al (2021) there is evidence of: (a) a lack of knowledge, experience, demonstration, and observation of teaching practices in the use of digital technologies in the classroom; (b) lack of opportunities to reflect on the attitude toward technologies, on the teaching experience or on the role and challenges that technologies present to the educational world; (c) insufficient technical-pedagogical advice for the design and development of digital educational resources and for the use of media; (d) lack of collaborative work in the teaching profession; (e) lack of motivation, incentives, and time for the effective integration of technologies in the classroom; (f) need to assess the digital competence of teachers in order to design appropriate training for teachers. Moreover, in a very current study by Dikmen (2022), teachers with good pedagogical-technological competence are found to be more interested in educational technologies and we notice an increase in their expectations regarding results coming from the use of instrumental technologies. Furthermore, teachers end up perceiving themselves as more qualified.…”
Section: Integration Of Digital Technologies In Classroom Contextsmentioning
confidence: 71%
“…If we look at the research conducted by Voithofer and Nelson (2021) who found that faculty members were increasingly integrating technology into curricula and teaching but that the level of TPACK adoption was quite low and that TPACK concepts differed greatly, we may wonder whether technology integration into other courses (that are not computer science oriented) is sufficient for the development of TPACK, or whether it is still necessary to offer specific courses to teach students how to properly integrate technology into teaching. In doing so, we should always take into account that the influence of will and desire of the individual teacher is another important factor to be taken into account, which Dikmen and Demirer (2022) emphasize in their research. Dikmen and Demirer (2022) The advantages of this longitudinal study are the comparison of the level of pedagogical and technological knowledge of students, future teachers at the beginning and end of their studies and determining the connection between higher knowledge of students and the study program they attend.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, we should always take into account that the influence of will and desire of the individual teacher is another important factor to be taken into account, which Dikmen and Demirer (2022) emphasize in their research. Dikmen and Demirer (2022) The advantages of this longitudinal study are the comparison of the level of pedagogical and technological knowledge of students, future teachers at the beginning and end of their studies and determining the connection between higher knowledge of students and the study program they attend. The disadvantages of this research are the small number of respondents and the self-assessment of students, where there may be a potential for giving socially desirable answers.…”
Section: Discussionmentioning
confidence: 99%